Effect of a karst system (France) on extended spectrum beta-lactamase (ESBL)-producing Escherichia coli. (15th February 2023) - Henriot, Charles P.; Celle, Hélène; Klaba, Victor; Biguenet, Adrien; Miège, Cécile; Daval, Amandine; Amiotte-Suchet, Philippe; Beugnot, Jean-Charles; Karbowiak, Thomas; Bertrand, Xavier
Highlights: The effect of karst on ARB has been investigated in a French karst hydrosystem. Similar ESBL-Ec (concentration, genetic characteristics) upstream/downstream karst. No filtration effect of karst on ESBL-Ec. Karst aquifers are widely exposed to the dissemination of ARB. Abstract: Karst aquifers are an important water resource worldwide particularly exposed to anthropogenic pollution, including antibiotic-resistance. The release of antibiotic-resistant bacterial pathogens in the environment is a major public health challenge worldwide. In this One Health study, we aimed to determine the effect of karst on antibiotic-resistant bacteria. For this purpose, we determined the concentrations of extended-spectrum β-lactamases-producing Escherichia coli (ESBL-Ec) for 92 weeks in a rural karst hydrosystem providing drinking water. ESBL-Ec isolates (n = 130) were sequenced by whole genome sequencing. We analysed the isolates at different levels of granularity, i.e., phylogroup, sequence type, presence of antibiotic-resistance genes, mutations conferring antibiotic-resistance, and virulence genes. The ESBL-Ec concentrations were spatially and temporally heterogeneous in the studied karst hydrosystem. ESBL-Ec isolates survived in the karst and their concentrations were mostly explained by the hydrodynamic of the hydrosystem. We demonstrate that the studied karst has no filtration effect on ESBL-Ec, either quantitatively ( i.e., in the ESBL-Ec concentrations) or qualitatively ( i.e., in the genetic characteristics of ESBL-Ec isolates). Graphical abstract: Image, graphical abstract